ANALISIS WACANA BERITA PEMKOT BANDUNG OPERASIKAN KEMBALI BIOSKOP PADA MEDIA ONLINE PIKIRANRAKYAT.COM EDISI 09 OKTOBER 2020 - Vera Hermawan; Dhini Ardianti; Desi Oktaviani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2021)
The results show that, in the text dimension pikiranrakyat.com provides more explanation about the process of opening a cinema from various stages prepared by the government for cinema entrepreneurs, as well as describing the regulations that must be applied in the cinema, the news text is also equipped with comments and responses from authorities on the policy of opening cinemas in Bandung city to strengthen news information. In the dimension of social cognitions, pikiranrakyat.com constructs news from various perspectives, starting from the policy of opening cinemas, the government, and the Bandung City health office regarding the anticipation of a new cluster spike in cinemas and the revocation of cinema permits that violate the agreement rules. Meanwhile, in the social context dimension, pikiranrakyat.com acts as a medium that mediates or the intermediary party in providing information on policies taken by the government to open cinemas during the pandemic.